The Representation of the Hero’s Journey Through Film Elements in Andrew Adamson’s The Chronicles of Narnia: The Lion the witch and the Wardrobe (2005) - Juwita Putri, Irman Nurhapitudin, Hasbi Assiddiqi (Lembaga Bale Literasi, 2025)
This study examines how Campbell's Hero's Journey is represented through cinematographic elements in The Chronicles of Narnia: The Lion, the Witch and the Wardrobe (2005), directed by Andrew Adamson. Previous studies applying Campbell's framework to cinematic narratives have predominantly treated the Hero's Journey as a story-level template, identifying narrative stages without examining how those stages are visually constructed. This study therefore addresses the following research question: how is Campbell's Hero's Journey represented through cinematographic elements in The Chronicles of Narnia: The Lion, the Witch and the Wardrobe (2005)? To answer this question, the study employs Campbell (2004) Hero's Journey as its primary analytical framework, supported by film theories proposed by Sikov (2010) and Petrie and Boggs (2018) covering shot types, spatial composition, foreground framing, and lighting. Using a qualitative content analysis method, the research examines selected scenes through repeated close viewing to identify how cinematographic elements construct the symbolic and psychological meaning of each Hero's Journey stage across the three phases of Departure, Initiation, and Return. The findings indicate that cinematographic elements in the film do not merely illustrate narrative events but actively produce monomythic meaning, with visual language frequently preceding dialogue as the primary mechanism of narrative construction. The study further identifies a structural adaptation in which the monomyth is distributed across four collective protagonists rather than a singular hero, a pattern consistently reinforced through collective framing. These findings suggest that Campbell's framework, when applied to film, operates not only as a narrative model but as a cinematographic one, extending its applicability beyond mythology and literary studies into the domain of visual media analysis.